2015
DOI: 10.1111/ibi.12245
|View full text |Cite
|
Sign up to set email alerts
|

Experimental enlargement of nest size does not increase risk of predation or brood parasitism in the Great Reed Warbler Acrocephalus arundinaceus

Abstract: We assessed whether nest size affects the probability of nest loss using dyads of large and small (large being twice the size of small) inactive Great Reed Warbler Acrocephalus arundinaceus nests placed at similar sites in Great Reed Warbler territories. Large nests were not predated significantly more frequently than small nests. Experimentally enlarged active Great Reed Warbler nests suffered non‐significantly higher predation compared with non‐manipulated control nests. Our experiments did not support the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…Nevertheless, larger nests could suffer from a greater predation pressure (Møller , Biancucci and Martin ). Jelínek et al () tested this assumption in enlarged and control great reed warbler nests (the same as in the present article) and found only marginally non‐significant trend to higher predation of enlarged nests. Moreover, they used also dyads of large and small inactive great reed warbler nests and found no difference in predation rate between these two groups.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Nevertheless, larger nests could suffer from a greater predation pressure (Møller , Biancucci and Martin ). Jelínek et al () tested this assumption in enlarged and control great reed warbler nests (the same as in the present article) and found only marginally non‐significant trend to higher predation of enlarged nests. Moreover, they used also dyads of large and small inactive great reed warbler nests and found no difference in predation rate between these two groups.…”
Section: Discussionsupporting
confidence: 62%
“…In magpies, the additional cost of large nests probably lies in greater probability of parasitism by great spotted cuckoos Clamator glandarius which preferably parasitize larger nests belonging to parents of better quality (Soler et al ). Our population of great reed warblers suffers from intensive parasitism by the common cuckoo, but a preference for larger nests was never found in this brood parasite neither in natural (Moskát and Honza , Jelínek et al ) nor in experimental conditions (Jelínek et al ). Nevertheless, larger nests could suffer from a greater predation pressure (Møller , Biancucci and Martin ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, because this color signal is expressed in the eggs, the female's potential mortality risk due to the expressed sexual signal should be lower than in species with ornamented females, from the perspective of detection by predators. Nest size has also been used as a form of signal by males in the Great Reed Warbler (Acrocephalus arundinaceus) (Jelínek et al 2016), and has been indicated to have no effect on nest predation or parasitism in the field (Jelínek et al 2015). Moreover, female feather carrying in the nest has also recently been proposed to affect male investment (Garcia-Navas et al 2015).…”
Section: The Importance Of a Less Costly Signalmentioning
confidence: 99%
“…The optimal egg-laying strategy proposes that when there are su ciently many available nests at a given time, cuckoo females should prefer the nest made by the best quality hosts (Hauber 2001;Parejo and Avilés 2007;Jelínek et al 2014). In this scenario, cuckoos may select larger nests associated with increased tness because larger nests may indicate superior parenting ability (Soler et al 1998;de Neve et al 2004;Avilés et al 2009;Jelínek et al 2015). A study spanning eight consecutive years showed that large magpie (Pica pica) nests were more likely to be parasitized by great spotted cuckoos (Clamator glandarius) than smaller nests when cuckoos have a larger availability of host nests among which to choose.…”
Section: Introductionmentioning
confidence: 99%